Amoxicillin-clavulanic Acid and Trimethoprim/Sulphamethoxazole Combination Therapy for Actinomycetoma in an Elderly Farmer: A Case Report - Sandra Arora; Jahanvi Goyal; Sanjeev B Gupta; Aayush Gupta (Journal of Clinical and Diagnostic Research)
Actinomycetoma is a chronic, localised, progressive granulomatous infection of the skin and subcutaneous tissues, typically affecting the lower extremities. It is caused by Actinomycetes bacteria, which are commonly found in soil and water. The infection usually results from minor trauma, such as walking barefoot or exposure to thorny vegetation. Upon inoculation, the bacteria form grains that help evade the host immune response, facilitating the establishment of infection. It is characterised by discharging sinuses and the presence of granules. This condition predominantly affects individuals in rural, resource-limited areas with limited access to healthcare. Although it affects both men and women, men are more commonly affected due to occupational exposure. The disease progresses slowly, often leading to severe complications, including tissue destruction and sinus tract formation, with amputation being the only option in advanced cases. Authors hereby report a case of Actinomycetoma in an 86-year-old male farmer who presented with painful erythematous nodules and purulent discharge from lesions on his left leg for the past four years. The diagnosis was established through clinical, histopathological and microbiological investigations, including Gram stain, Gomori Methenamine Silver (GMS), and Periodic Acid-Schiff (PAS) stain. Treatment with a combination of amoxicillin-clavulanic acid and trimethoprim/sulphamethoxazole was initiated. This led to a complete resolution of the condition within three weeks, demonstrating the efficacy of this treatment as a safe and cost-effective option. This case highlights the importance of early diagnosis and appropriate treatment for Actinomycetoma, emphasising the value of affordable therapeutic interventions.